Дослідження методів розробки IT-проєкту платіжного шлюзу - Гімонов, С. В. (ХНУРЕ, 2024)
The focus of this research is on investigating methods and models for an IT project in the development of a payment gateway. Specifically, the research explores the process of building recommender systems that provide personalized recommendations for consumers based on their preferences and the characteristics of the products or services being offered.
Keywords: IT-проєкт; фінансові дані